Photosynthesis in dynamic and rapidly changing light: the physiology of a cyanobacterium in a photobioreactor - Andersson, Bjoern, author; Peers, Graham, advisor; Pilon, Marinus, committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2017)
Mass cultivation of aquatic phototrophs in photobioreactors (PBRs) has the potential to produce sustainable biofuels thus reducing net carbon emission and associated climate change. In order to make PBRs productive enough to be economically viable, the biomass accumulation rate and cell density at harvest needs to be high. However, early productivity estimates based on controlled laboratory experiments has not scaled-up to industrial size PBRs. One major reason is that the growth rates in high density, low maintenance PBRs is severely reduced compared to laboratory conditions. This is likely a consequence of the fluctuating light environment. The photophysiological response of algae or cyanobacteria to growth in outdoor PBRs has not been well characterized. The work presented in this thesis aimed to describe the complexity of the light environment in a small-scale PBR and also the physiological response of photoautotrophs to growth in this environment. A dense culture of the cyanobacterium Synechocystis sp. PCC 6803 was grown in a bench-top PBR with an incident light that followed a sinusoidal function peaking at 2000 µmol photons m-2 s-1. These conditions approximate natural sunlight. The diurnal changes in the light environment of the bench top PBR was quantified from the perspective of a single-cell, using a computational fluid dynamic approach (Chapter 1). Due to self-shading within the dense culture, single cells experienced rapid fluctuations (~6 s) between 2000 and <1 µmol photons m-2 s-1, and on average the integrated irradiance per cell was 85% lower than the incident irradiance (mean per cell: 184 µmol photons m-2 s-1). We investigated the activity of photoprotective mechanisms under our realistic light environment, using pulse amplitude modulated (PAM) fluorometery and membrane inlet mass spectrometry (MIMS). Contrary to common assumption we found no evidence for net-photodamage or non-photochemical quenching (NPQ) activity in situ (Chapter 1). In an ex situ experiment we found that alternative electron transport (AET) dissipated 50% of electrons from photosystem II, preventing them from being used for carbon fixation. This indicates that AET, and not NPQ is the first photoprotective mechanism Synechocystis uses under dynamic and fluctuating light. These results have important applications for genetic and metabolic engineering strategies that commonly targets NPQ and photodamage as a way to boost productivity of PBRs. Since, AET caused the main diversion from linear electron transport and carbon fixation, this mechanism should be investigated as a genetic engineering strategy. Samples were also taken to monitor the response of the transcriptome with high temporal precision around the day/night transitions (Chapter 2). The transcriptome data showed that 74% of all genes exhibited some modification in transcription across the diel cycle. In my preliminary analysis of the data (Chapter 2), I found that the major components of photosynthetic light harvesting and electron transport complexes increased in abundance during the whole light period. This is commonly observed in cultures growth under sub-saturating light intensities but not high light stress. Furthermore, few other high light stress responses were observed in the transcriptome. There was little diel variation in transcriptional activity of molecular chaperones (dnaK, hsp, groE families), proteases (ftsH and Deg families), high light inducible proteins (hli), and reactive oxygen species scavengers (superoxide dismutase and catalase peroxidase) that are responsive to high light stress. The flavodiiron proteins are considered the main player of AET in cyanobacteria and are up-regulated transcriptionally under light and inorganic carbon stress. Interestingly, there were no increased abundance in transcripts of the flavodiiron proteins during the light period in my experiment. Assuming that transcript abundance correlates with protein abundance this could mean that either these genes are constituently expressed or that other enzymes may exist that are responsible for the AET. Further analysis of the transcriptomic data and future proteomic analysis may uncover putative genes whose transcriptional pattern indicates that they may play a role in AET under fluctuating light.
Zip file contains supplementary video, no sound.
Keywords: dynamic light; photoprotection; computational fluid dynamics; photosynthesis; photobioreactor